2001
DOI: 10.1051/forest:2001144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acorn storage duration and parental tree on emergence and physiological status of Cork oak (Quercus suber L.) seedlings

Abstract: -This study was conducted to evaluate how parental trees and seed storage duration influenced subsequent seedling physiological status and growth. Seedling emergence rate was higher than 90% independently of the duration of seed storage or parental trees. Seed storage shortened significantly the time and increased the uniformity of seedling emergence. Consequently, the delayed seedling emergence from fresh seeds could be explained by epicotyl dormancy. Seed size varied with parental tree. Seedling growth rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
3
15
0
4
Order By: Relevance
“…These similar results are not surprising because the availability of a given resource in the seed is largely a function of the total seed mass (Kitajima and Fenner 2000). The positive correlation between seed size and seedling biomass documented here concurs with the results of numerous studies within the family Fagaceae (Aizen and Woodcock 1996;Kormanik et al 1998;Bonsil 1998;Merouani et al 2001). Furthermore, the seed reserve and seedling biomass relationship we documented is similar to Bonsil (1998), who found that cotyledon excision significantly reduced subsequent seedling growth of both Q. rugosa and Q. laurina.…”
Section: Discussionsupporting
confidence: 92%
“…These similar results are not surprising because the availability of a given resource in the seed is largely a function of the total seed mass (Kitajima and Fenner 2000). The positive correlation between seed size and seedling biomass documented here concurs with the results of numerous studies within the family Fagaceae (Aizen and Woodcock 1996;Kormanik et al 1998;Bonsil 1998;Merouani et al 2001). Furthermore, the seed reserve and seedling biomass relationship we documented is similar to Bonsil (1998), who found that cotyledon excision significantly reduced subsequent seedling growth of both Q. rugosa and Q. laurina.…”
Section: Discussionsupporting
confidence: 92%
“…This positive effect of seed size on seedling growth affects not only final seedling size, but also its growth rate as shown in Merouani et al [20]. These authors confirmed that seedlings of Quercus suber originating from the largest seeds had also the fastest growth rate.…”
Section: Introductionsupporting
confidence: 76%
“…In many tree species, initial seedling growth is positively correlated with seed mass (Howe and Richter 1982;Vaughton and Ramsey 1998;Sousa et al 2003;Kennedy et al 2004), and this is also true in oak species (Merouani et al 2001;Grossman et al 2003). Furthermore, larger oak acorns have a higher germination rate (Gomez 2004;Tilki 2010).…”
Section: Biological Aspectsmentioning
confidence: 86%